As avaliações em larga escala e o currículo no estado de São Paulo: A realidade escolar desvelando as lógicas subjacentes - Bertagna, Regiane Helena [UNESP]; Polato, Amanda [UNESP]; De Mello, Liliane Ribeiro [UNESP] (My University, 2018)
This research aims to analyze the relation between large-scale assessments, the Sao Paulo state general school curriculum and the management-like strategies adopted in a countryside Sao Paulo school. For this end a qualitative-ethnographic research was developed, including the data collection of: school meetings, Portuguese and Mathematics classes in 9th grade and also interview sessions with teachers faculty and staff personnel. Data collection revealed the target school has a strong influence of the Sao Paulo State Assessment System for School Performance (SARESP) in its management organization which relates to the official state curriculum. Also the guidelines for a good school performance in the assessments are worrisome either for teachers and students, where they undergo a workload related to management logics (business/private) once they are driven to a privative bias as a solution for education quality improvement.
Keywords: Curriculum; Large-scale assessments; Managerialism; Organization of school work; Privatization